2013
DOI: 10.1016/j.jmbbm.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Application of viscoelastic fracture model and non-uniform crack initiation at clinically relevant notches in crosslinked UHMWPE

Abstract: The mechanism of crack initiation from a clinically relevant notch is not well-understood for crosslinked ultra high molecular weight polyethylene (UHMWPE) used in total joint replacement components. Static mode driving forces, rather than the cyclic mode conditions typically associated with fatigue processes, have been shown to drive crack propagation in this material. Thus, in this study, crack initiation in a notched specimen under a static load was investigated. A video microscope was used to monitor the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…angles and demonstrated rippling associated with larger surface strains before rupture [6,7,27,[42][43][44]. Such features have been associated with local Mode III damage and the gradual accumulation of damage during cyclic loading in a region ahead of the crack tip known as a "process zone" [45,46]. Fracture surfaces from both the RXLPE and VXLPE materials show a marked reduction in these ductile features, consistent with their higher strength from crosslinking.…”
Section: Resultsmentioning
confidence: 88%
“…angles and demonstrated rippling associated with larger surface strains before rupture [6,7,27,[42][43][44]. Such features have been associated with local Mode III damage and the gradual accumulation of damage during cyclic loading in a region ahead of the crack tip known as a "process zone" [45,46]. Fracture surfaces from both the RXLPE and VXLPE materials show a marked reduction in these ductile features, consistent with their higher strength from crosslinking.…”
Section: Resultsmentioning
confidence: 88%
“…The findings for crosslinked UHMWPE [27], as well as findings for non-crosslinked UHMWPE [33] support that static creep loading is a dominant mechanism for crack propagation in crosslinked UHMWPE. As a result of this finding, previous studies by the authors [34,35] focused on the role of static creep loading on determining crack initiation time and crack propagation velocity from a notch in crosslinked UHMWPE. It was found that the Williams' viscous fracture model [36] was able to predict both crack initiation and propagation velocity from a notch in two crosslinked UHMWPE formulations.…”
mentioning
confidence: 75%
“…A notch radius of 0.25 mm was implemented. The test specimen geometry was the same as that used in a previous study by the authors [34]. A total of 24 round compact tension specimens were tested under various cyclic loading conditions (described, below).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover the crack initiation from a notch in UHMWPE is a complex phenomenon that is governed by the viscoelastic fracture theory (Sirimamilla [2012]). …”
Section: Creep Testing and Modelingmentioning
confidence: 99%